Penggunaan Model Pembelajaran Numbered Head Together (NHT) untuk Meningkatkan Hasil Belajar Matematika Siswa - Fadilah, Nur; Hidayah, Shofia; Santoso, Wahyudi Teguh (Polinomial : Jurnal Pendidikan Matematika, 2026)
This study is a Classroom Action Research (CAR) aimed at improving the mathematics learning outcomes of Grade XII Language 2 students on the topic of combinatorics through the application of the Numbered Heads Together (NHT) method. The research subjects consisted of 30 students from Grade XII Language 2 at MA Nurul Jadid. Data were collected through written tests and interviews with teachers and students. The implementation of the NHT method was carried out in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The results showed that the average score in the pre-cycle stage was 56.5. After implementing the NHT method in Cycle 1, the class average increased to 71.2, and in Cycle 2 it further increased to 83.4. These findings demonstrate that the application of the NHT method can improve students’ learning outcomes. Data analysis was conducted using both quantitative and qualitative descriptive methods. Quantitative data were obtained from students' learning test results, while qualitative data were obtained from observation results.